Answer:
Step-by-step explanation:
Answer:
x=1
Step-by-step explanation:
So, first you make sure to multiply the parenthesis by the negative so then it would be,
-x-3=2x-6
Then you add the -3 from the right to the other side
so, -x=2x-3
Then you want all the X variables to one side so you subtract the 2x to both sides.
so, -3x=-3
divide both by -3
x=1
Answer:
X' = (2, -3)
Y' = (7, -9)
Z' = (10, -2)
Step-by-step explanation:
to find the translation of each point substitute the x and y with the the numbers
eg; X ( -5,2) the x is 5 and the y is 2
so -5 + 7 = 2 (the x value)
2 - 5 = -3 ( the y value)